Inactivation of plant pathogenic bacterium Ralstonia solanacearum in drainage solution from hydroponic system by a rotating advanced oxidation contactor equipped with TiO2/zeolite composite sheets. (August 2022) - Nomura, Youhei; Koga, Koutaro; Ohnishi, Kouhei; Fukahori, Shuji; Fujiwara, Taku
Abstract: A rotating advanced oxidation contactor (RAOC) equipped with TiO2 /zeolite composite sheets was developed to inactivate the plant pathogenic bacterium Ralstonia solanacearum in drainage solution (DS) from a hydroponic system. The inactivation efficiency of R. solanacearum in DS and pure culture solution (PS) by the RAOC was compared with that achieved by a submerged composite sheet photocatalysis reactor (SSPR). The initial number of living bacteria ( N 0 ) was adjusted to around 10 6 –10 7 CFU mL −1 . The inactivation efficiency of R. solanacearum by the SSPR at 4.0 × 10 7 CFU mL −1 of N 0 significantly decreased compared with that at 1.8 × 10 6 CFU mL −1 of N 0 owing to the attenuation of UV intensity by light absorption and scattering by solids derived from R. solanacearum, while the RAOC achieved >2-log inactivation during 24 h of treatment regardless of N 0 . The inactivation of R. solanacearum by the RAOC decelerated after 6 h, possibly because of competition for reactive oxygen species between R. solanacearum and products accumulated by inactivation of R. solanacearum . The ratio of rate constants for inactivation of R. solanacearum in DS to that in PS by the RAOC was 8 times that for the SSPR. This shows that the RAOC greatly mitigates the light attenuation and inhibitory effects of coexisting substances on inactivation of R. solanacearum in the DS. The RAOC is therefore a promising and upscalable photocatalytic reactor for efficient inactivation of R. solanacearum in DS. Graphical abstract: Unlabelled Image Highlights: A rotating advanced oxidation contactor (RAOC) with TiO2 /zeolite sheets was used. The RAOC was used to disinfect drainage solution (DS) from hydroponic system. Inactivation of Ralstonia solanacearum in the DS by the RAOC was investigated. The RAOC mitigated inhibition of photocatalysis by coexisting substances in the DS. The RAOC efficiently inactivated R. solanacearum in DS.